Closing Legal Loopholes in Public-Private Partnership Schemes for Waste Management in Indonesia - Mappuji, M. Raihan; Sarsito, Akiyo Ramadhan; Miolo, Tsaquila Shafa Raissa; Saputra, Budi (Journal of Infrastructure Policy and Management, 2025)
In recent years, Public-Private Partnership (PPP) schemes have been increasingly used in Indonesia. PPP schemes attract foreign investment because they are cost-efficient. However, the waste-management sector has not reaped these benefits due to a gap in sectoral regulation. This paper addresses the issues of legal loopholes and proposes fundamental elements that should be included in future waste-management PPP legislation. The results of this paper are intended to assist legislators in developing future regulations for the sector. We employed a qualitative research method, specifically through a normative legal approach by relying on international standards and comparative provisions across jurisdictions. Our analysis identifies three main aspects that future legislation should include. First, waste-management PPPs require an explicit legal and policy framework that governs financing schemes, including clear and investor-friendly principles and options. Second, tax incentives are essential. To enable effective participation, legislation should provide tax and customs incentives (e.g., tax holidays and exemptions). Third, incentives related to local content requirements (TKDN) are highly required. One persistent barrier to market entry in PPP projects is strict TKD requirements and high import costs. Therefore, we propose TKDN mechanisms that incentivize investors to participate in the projects by reducing TKDN thresholds in the sector.